2023
DOI: 10.1021/acs.est.3c07526
|View full text |Cite
|
Sign up to set email alerts
|

United States Influenza 2022–2023 Season Characteristics as Inferred from Wastewater Solids, Influenza Hospitalization, and Syndromic Data

Mary E. Schoen,
Amanda L. Bidwell,
Marlene K. Wolfe
et al.

Abstract: Influenza A virus (IAV) causes significant morbidity and mortality in the United States and has pandemic potential. Identifying IAV epidemic patterns is essential to inform the timing of vaccinations and nonpharmaceutical interventions. In a prospective, longitudinal study design, we measured IAV RNA in wastewater settled solids at 163 wastewater treatment plants across 33 states to characterize the 2022–2023 influenza season at the state, health and human services (HHS) regional, and national scales. Influenz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…During the time between sample collection and transport (0–3 days), we expect minimal losses of the RNA target based on results of IAV RNA persistence studies . Upon receipt of the laboratory, samples are processed immediately to measure IAV M gene and PMMoV gene concentrations in the solid fraction of wastewater; the solid fraction was chosen for measurements as work indicates that these targets are enriched orders of magnitude in solids compared to liquids in wastewater , Since the methods are described in detail elsewhere, , they are not provided in the main text and are summarized in the SI. PMMoV is an endogenous plant virus present in wastewater and serves as an internal process control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the time between sample collection and transport (0–3 days), we expect minimal losses of the RNA target based on results of IAV RNA persistence studies . Upon receipt of the laboratory, samples are processed immediately to measure IAV M gene and PMMoV gene concentrations in the solid fraction of wastewater; the solid fraction was chosen for measurements as work indicates that these targets are enriched orders of magnitude in solids compared to liquids in wastewater , Since the methods are described in detail elsewhere, , they are not provided in the main text and are summarized in the SI. PMMoV is an endogenous plant virus present in wastewater and serves as an internal process control.…”
Section: Methodsmentioning
confidence: 99%
“…Wastewater surveillance of influenza A has been implemented across the US, and concentrations of viral RNA in wastewater have been shown to align with clinical surveillance metrics including influenza-like illness, hospitalizations, and deaths. As a result, it is becoming a routine public health tool for influenza outbreaks and provides low-cost, real-time, population level data on influenza outbreaks, particularly in locations with limited clinical testing. , The utility of these data and responses are predicated on the assumption that the majority of the contributions to these measurements are from human sources, rather than influenzas with zoonotic potential such as H5N1 and H7N9. , Recent increases in the spread of HPAI to new species, particularly subtype H5N1 clade 2.3.4.4b spread in dairy cattle, have raised questions about wastewater contributions from avian and bovine sources. , …”
Section: Introductionmentioning
confidence: 99%
“…Upon receipt of the laboratory, samples are processed immediately to measure IAV M gene and PMMoV gene concentrations in the solid fraction of wastewater. Since the methods are described in detail in several different publications 8,19 , they are not provided in detail here. PMMoV is an endogenous plant virus present in wastewater and serves as an internal process control.…”
Section: H5 Assay Designmentioning
confidence: 99%
“…Wastewater surveillance of influenza A has been implemented across the United States, and concentrations of viral RNA in wastewater have been shown to align with clinical surveillance metrics including influenza-like illness, influenza hospitalizations, and deaths. [7][8][9][10] As a result, it is becoming a routine public health tool for influenza outbreaks and provides low-cost, real-time, population level data on influenza outbreaks, particularly in locations with limited clinical testing 11 . The utility of these data and responses are predicated on the assumption that the majority of the contributions to these measurements are from human sources, rather than influenzas with zoonotic potential such as H5N1 and H7N9 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that wastewater concentrations of RSV RNA correlate with disease occurrence within the communities contributing to wastewater; however, these studies have been conducted at small geographic scales. We have previously demonstrated that wastewater-based measurements of influenza can be related to traditional surveillance metrics across the US . In this study, we use data from across the US to investigate how RSV RNA concentrations in the solids from wastewater relate to traditional disease metrics during the 2022–2023 RSV season.…”
Section: Introductionmentioning
confidence: 99%